Kinetics of the cathodic discharge of ammonium ion dissolved in dimethylsulfoxide on platinum - Martínez, C. (1973)
The cathodic discharge of ammonium ion dissolved in DMSO solution on platinum electrodes in the temperature range from 25 to 44 °C yields ammonia and hydrogen at the ratio 2 : 1. The kinetics of the reaction was studied both under stationary and non-stationary conditions and reveals an influence of the treatment of the electrode surface. The kinetic parameters were interpreted with a reaction mechanism involving the participation of adsorption competition between either solvent or impurity molecules and hydrogen atoms, assuming the recombination of these adatoms is rate determining.